2015
DOI: 10.4314/ijbcs.v8i6.12
|View full text |Cite
|
Sign up to set email alerts
|

Vulnérabilité des cossettes issues de quelques cultivars d’igname à l’attaque de Dinoderus porcellus Lesne (Coleoptera: Bostrichidae) en conditions de laboratoire

Abstract: Dinoderus porcellus Lesne a été récemment identifié comme un véritable ravageur des stocks de cossettes d'igname en Afrique de l'Ouest. En conséquence, plusieurs méthodes de lutte ont été testées ou envisagées contre ce ravageur et comprennent, entre autres, l'utilisation des cultivars d'ignames résistants à l'insecte. Dans la présente étude, le comportement de quatre lots de cossettes issues des quatre cultivars d'igname suivants : Otoukpanan, Singor, Kprakpra et Portchahabim face à D. porcellus a été observé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The beetle D. porcellus was reared using healthy yam chips as described by Onzo et al [17]. Yam chips were sterilized in an oven at 105 ∘ C for 2 hours to kill hidden insects and their eggs.…”
Section: Rearing Of Dinoderus Porcellusmentioning
confidence: 99%
“…The beetle D. porcellus was reared using healthy yam chips as described by Onzo et al [17]. Yam chips were sterilized in an oven at 105 ∘ C for 2 hours to kill hidden insects and their eggs.…”
Section: Rearing Of Dinoderus Porcellusmentioning
confidence: 99%
“…Although the interaction between resistant yam chips and medicinal plants has not been significant, the high repellence observed on D. porcellus could be due, on one hand to the effect of physicochemical compounds in yam chips and in the other hand to the presence of repulsive volatile substances in the leaves of each of the three medicinal plants (Table 1). Indeed, the color, smell and texture of yam chips could play a determining role in the repulsion of D. porcellus (Onzo et al, 2015). In addition, the triterpenoid, tannins and saponoside contained in the leaves powder of B. ferruginea (Addae-Mensah and Achenbach, 1985), B. sapida (Ubulom et al, 2012) and K. senegalensis (Makut et al, 2008) are known repulsive for phytophagous insects because of vapor acting on their olfactory receptors (Moore and Lenglet, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…D. porcellus was collected from infested yam chips purchased from Dassa market and maintained on healthy yam chips in the laboratory using the method described by Onzo et al (2015). The experimental plan was composed of cylindrical plastic boxes opened at one extremity.…”
Section: Rearing Of D Porcellusmentioning
confidence: 99%
See 1 more Smart Citation
“…The agro-morphological [33] and molecular characterization [34] of these 64 landraces revealed the existence of many duplicates and classified them in 24 morphotypes [33]. Choosing based on their good agronomic and culinary characteristics, the susceptibility of 5 of the 64 landraces identified as given resistant chips were tested in the laboratory by Onzo et al [35]. These authors demonstrated the existence of a differential susceptibility between the different tested landraces with respect to D. porcellus with Singor and Portchahabim landraces as the least vulnerable to the attacks of this pest.…”
Section: Resistant Varietiesmentioning
confidence: 99%